The role of neuromuscular ultrasound in diagnostics of peripheral neuropathies induced by cytostatic agents or immunotherapies - Stefanie Hartinger; Jakob Hammersen; Niklas A. Leistner; Anna Lawson McLean; Clemens Risse; Christian Senft; Stefanie Schütze; Bianka Heiling; Matthias Schwab; Irina Mäurer (Acta Neuropathologica Communications, 2023)
Abstract A relevant number of cancer patients who receive potentially neurotoxic cytostatic agents develop a chemotherapy-induced peripheral neuropathy over time. Moreover, the increasing use of immunotherapies and targeted agents leads to a raising awareness of treatment-associated peripheral neurotoxicity, e.g., axonal and demyelinating neuropathies such as Guillain–Barré-like syndromes. To date, the differentiation of these phenomena from concurrent neurological co-morbidities or (para-)neoplastic nerve affection as well as their longitudinal monitoring remain challenging. Neuromuscular ultrasound (NMUS) is an established diagnostic tool for peripheral neuropathies. Performed by specialized neurologists, it completes clinical and neurophysiological diagnostics especially in differentiation of axonal and demyelinating neuropathies. No generally approved biomarkers of treatment-induced peripheral neurotoxicity have been established so far. NMUS might significantly extend the repertoire of diagnostic and neuromonitoring methods in this growing patient group in short term. In this article, we present enlargements of the dorsal roots both in cytostatic and in immunotherapy-induced neurotoxicity for the first time. We discuss related literature regarding new integrative applications of NMUS for cancer patients by reference to two representative case studies. Moreover, we demonstrate the integration of NMUS in a diagnostic algorithm for suspected peripheral neurotoxicity independently of a certain cancer treatment regimen emphasizing the emerging potential of NMUS for clinical routine in this interdisciplinary field and prospective clinical trials.